Strengthening Students’ Communicative Competence in Basic English Levels - Perez, Celso; Rodríguez, Teresa; Lezama, Verónica; Méndez, Blanca (CIEX JOURNAL, 2019)
This study aims to identify the strategies and activities that promote the development of oral skills for students in a technical private language school in San Juan Teotihuacan, Mexico. The information was collected using a questionnaire to English language learners and to English language teachers. Findings suggest that students feel motivated to speak English in the classroom by using some strategies to help themselves to improve and develop communicative competence. It was also identified that most teachers have used teaching materials such as videos and visual aids to develop the students’ oral skills; improve pronunciation, motivate students to speak English, and increase students’ vocabulary.